Highly Cited Articles in Health Care Sciences and Services Field in Science Citation Index Expanded - Hsu, Y.-H. E.; Ho, Y.-S. (Methods of Information in Medicine, 2014)
Objective: This study aimed to identify and analyze characteristics of highly cited articles published in the Web of Science category of health care sciences and services from 1958 to 2012.Methods: Articles that have been cited at least 100 times were assessed regarding publication outputs, distribution of outputs in journals, publications of authors, institutions, countries as well as citation life cycles of the articles with the highest total citations since its publication up to 2012 and the highest citations in 2012. Six bibliometric indicators were used to evaluate source countries, institutions, and authors. Total citations from the time the articles were first published to the end of 2012 and citations in 2012 only were applied. Additionally, Y-index was applied to evaluate publication characteristics of authors. A high percentage of authors had the same numbers of first author and corresponding author status of highly cited articles in health care sciences and services field.Results: Results showed that 890 of the most highly referenced articles, published between 1977 and 2009, had been cited at least 100 times. Medical Care and Journal of General Internal Medicine published the most highly cited articles. The United States produced 76% of highly cited articles and also published the most number of independent, internationally collaborative, first authored, corresponding authored, and single author highly cited articles. The Harvard University was the most productive institute and was number one for the total highly cited articles, inter-institutionally collaborative articles, single institution articles, first author articles, and corresponding author articles.Conclusions: The application of quantitative techniques in the analysis of highly cited articles can improve the researchers’ understanding of the directions in health care sciences and services field. Y-index is useful for the evaluation of contributing authors.
Keywords: Y-index; SCI-EXPANDED; bibliometric; top-cited articles; article life; health care sciences and services